Symposium 3: Learning and Living Technologies: A Longitudinal Study of First-Year Students’ Expectations and Experiences in the Use of ICT - Ramanau, Ruslan; Hosein, Anesa; Jones, Chris (Proceedings of the International Conference on Networked Learning, 2010)
This paper presents results from a longitudinal study on first-year students’ expectations and actual reported use of information and communication technologies (ICT) at university. The study was interested in firstly, knowing if students from the Net Generation (≤ 25 years) would appropriate more ICT time for both social life and leisure, and study purposes than older students, as this forms the basis for many Net Generation and Digital Natives claims about young people use of technology. Secondly, the impact of university type (place-based or distance-learning) on ICT use was explored. Data were analysed from two surveys that were part of the Economic Social Research Council (ESRC) funded project: The Net Generation Encountering eLearning at University. The first survey which asked for expected ICT time was sent at the beginning of the academic year. The second survey was sent towards the end of the academic year and asked for the actual time spent on using ICTs. Students studying 14 different courses in five different universities (four place-based and one distance-learning) in England took part in the study. The results showed that students underestimated their total ICT time (combined time for social life and leisure, and study purposes) by at least 1 hour per day. The Net Generation students were found to spend more time per day using ICT for social life and leisure purposes than the non-Net Generation students (2.2 vs 1.7 hrs). In contrast, the non-Net Generation students spent more ICT time on study than the Net Generation students (2.3 vs 1.9 hrs. It appears that younger generation students used ICT for social life and leisure more frequently and older students were more likely to use it for study. University mode of study also influenced how students appropriated their ICT time. Place-based university students spent at least one hour more per day on ICT than distance-learning university students. The results found differences across the two age groups were more noticeable at the place-based university than at the distance-learning university.